Heterogeneous expectations, boom-bust housing cycles, and supply conditions: A nonlinear dynamics approach - Roberto Dieci; Frank Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2015)
We combine a standard stock-flow housing market model, incorporating explicit relationships between house prices, the housing stock, and the rent level, with a parsimonious expectation formation scheme of housing market investors, reflecting an evolving mix of extrapolative and regressive expectation rules. The model results in a two-dimensional discrete-time nonlinear dynamical system. Based on realistic parameters, the model is able to generate endogenous boom-bust housing market dynamics with lasting periods of overvaluation and overbuilding. We thus exploit our model to investigate how real forces, in particular supply conditions, interact with expectations-driven housing market fluctuations.
Keywords: D84; R21; R31; 330; Housing markets; Speculation; Housing supply; Boom-bust cycles; Nonlinear dynamics